The demand for money in Austria - Bernd Hayo (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2000)
In this paper, the demand for real money M1, M2, and M3 is estimated for Austria. The modelling takes place within the framework of a small vector autoregression. To estimate the demand for money, two-equation error-correction models are constructed, which contain the short-run dynamics and the long-run economic equilibrium. It is found that a stable money demand exists for all monetary aggregates. The long-run equilibrium of M1, after accounting for a structural break in 1979, can be characterised as a classical type of money demand, with no interest rate effects and a unity elasticity of real GDP. In the case of M2 and M3, we find a unit coefficient on income and a significantly negative influence of a long-term interest rate. The statistical properties of the estimated short-run money demand equations – considering insample and out-of-sample (35 observations) tests – are generally very good.
Keywords: E41; C32; 330; monetary economics; money demand; Austria